1995
DOI: 10.1038/jcbfm.1995.8
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Evaluation of Superoxide Radical Production in Neural Cells under Various Culture Conditions: Application to Hypoxia

Abstract: Summary: To evaluate the potential deleterious influence of oxygen-derived free radicals following hypoxia in a model of primary culture of neurons obtained from the fetal rat brain, superoxide radicals were measured as a function of time in the extracellular medium. Neuronal cells were grown for 8 days in the presence or absence of serum, then incubated in a buffered Krebs-Ringer solu tion containing 60 j..l. M acetyl-cytochrome c. The rate of superoxide radical formation was quantified spectropho tometricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…However, studies on the effects of TBI preceding HSCT have mostly been limited to thyroid dysfunction. They have shown overt or, more frequently, subclinical hypothyroidism in 10-60% of patients, with a single dose more deleterious than a fractionated dose (25,26,27,40,41,42,43). Consistent with most previous studies, peripheral subclinical hypothyroidism was found in 12 (16%) patients in our studied population and was transient in five of these patients.…”
Section: Discussionsupporting
confidence: 91%
“…However, studies on the effects of TBI preceding HSCT have mostly been limited to thyroid dysfunction. They have shown overt or, more frequently, subclinical hypothyroidism in 10-60% of patients, with a single dose more deleterious than a fractionated dose (25,26,27,40,41,42,43). Consistent with most previous studies, peripheral subclinical hypothyroidism was found in 12 (16%) patients in our studied population and was transient in five of these patients.…”
Section: Discussionsupporting
confidence: 91%
“…Animals were cared for in accordance to the policy laid down by Animal Care Committee of Industrial Toxicology Research Centre and the Ethical Committee of the Centre approved Animal Experimentation. For neuronal cell culture 14-day-old embryos (Daval et al, 1995) and for glial cells 0-1-day-old pups were used (De et al, 1991). In brief, brains from 14-day-old rat fetus or from 1-day-old pups were dissected and kept in hanks balanced salt solution (HBSS) containing antibiotic and antimycotic.…”
Section: Neuronal and Glial Cell Culturementioning
confidence: 99%
“…Superoxide anion (O 2 -) generation was detected by employing two different methods; one was a spectrophotometric measurement of the reduction of acetyl cytochrome c (Si et al, 1997;Daval et al, 1995) …”
Section: Detection Of Superoxide Anion Generationmentioning
confidence: 99%